2022
DOI: 10.33603/jnpm.v6i1.5315
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi antara Keyakinan Belajar dan Pemahaman Konseptual Kalkulus pada Calon Guru Matematika

Abstract: Abstrak. Keyakinan adalah faktor penting dalam mempengaruhi praktek pembelajaran matematika di dalam kelas. Keyakinan belajar kalkulus diasumsikan memiliki korelasi dengan pemahaman konseptual kalkulus. Penelitian ini bertujuan untuk menguji hubungan antara keyakinan belajar kalkulus dan pemahaman konseptual kalkulus. Penelitian menggunakan metode survei dengan desain cross-sectional terhadap 65 orang calon guru matematika yaitu mahasiswa pendidikan matematika pada semester tiga dan lima. Data keyakinan belaja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…Student teacher candidates still experience conceptual ontological obstacles, namely conditions when students still do not understand the concepts used. The same fact was found in the research of Hoiriyah et al (2019) and Tamba et al (2022), namely that more than 60% of prospective teacher students failed the test that tested mathematical understanding. Based on the exposure to the facts of the literature, it can be concluded that the mathematical understanding of prospective teachers is still low.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Student teacher candidates still experience conceptual ontological obstacles, namely conditions when students still do not understand the concepts used. The same fact was found in the research of Hoiriyah et al (2019) and Tamba et al (2022), namely that more than 60% of prospective teacher students failed the test that tested mathematical understanding. Based on the exposure to the facts of the literature, it can be concluded that the mathematical understanding of prospective teachers is still low.…”
Section: Introductionsupporting
confidence: 77%
“…Several studies have been conducted studies related to the mathematical understanding of prospective student teachers. Arifin & Aprisal (2020) and Tamba et al (2022) are examples of researchers who conducted mathematical understanding studies specifically on the conceptual abilities of prospective teacher students. The research was conducted to analyze overall conceptual ability based on the indicators used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keyakinan berperan dalam setiap pengalaman belajar. Keyakinan adalah faktor penting dalam mempengaruhi praktek pembelajaran matematika di dalam kelas (Tamba et al, 2022). Dalam persiapan guru, ada spektrum keyakinan yang dianut secara mendalam, seringkali tidak teruji, yang memengaruhi bagaimana pendekatan guru masa depan dan praktik terhadap tugas belajar untuk mengajar dan pengetahuan yang mereka bangun dari pengalaman.…”
Section: Pendahuluanunclassified
“…Beberapa studi tentang keyakinan diantaranya mengeksplorasi tentang keyakinan hakikat matematika, keyakinan pembelajaran matematika dan keyakinan pengajaran matematika mahasiswa (Adnan & Zakaria, 2010), keyakinan tentang pengajaran dan pembelajaran serta relasinya dengan pengetahuan matematika dan perencanaan instruksional calon guru dan guru sekolah dasar (Lui & Bonner, 2016) serta korelasi keyakinan dengan pedagogical content knowledge calon guru matematika (Sumartini, 2022). Studi lainnya menyatakan bahwa calon guru tidak konsisten dalam hal keyakinan belajar (Tamba et al, 2022) dan beberapa keyakinan yang tampaknya bertentangan mengenai sifat matematika (White et al, 2006).…”
Section: Pendahuluanunclassified